Assessment of the morphological features, physiological and photosynthetic activity of the different cell forms of Symbiodiniaceae using microfluidic methods - Szabó, Milán; Szabó, Zoltán; Ábrahám, Ágnes; Nagy, Krisztina; Sass, László; Galajda, Péter; Vass, Imre (Frontiers in Photobiology, 2025)
The dinoflagellate algae Symbiodiniaceae live in endosymbiosis with Anthozoa, which is essential for the existence of coral reefs. The cells of Symbiodiniaceae exist in two distinct forms: the flagellated, motile form and the non-flagellated, coccoid form, which play specific roles in the life cycle of these algae. The regulation and distribution of the different cell forms have been intensively studied in the past, however, the behavior and changes of the cell cycle are less characterized under conditions that mimic the coral tissue versus the free living environment, e.g., by manipulating the viscosity of the medium and thereby altering cell motility. In this work, we applied precisely controlled microfluidic tools to manipulate the viscosity of the medium, using the polysucrose Ficoll. We found that by the application of Ficoll the diurnal cycle of the different cell forms undergoes remarkable changes, the motility of the cells decreases, and the motile phase of the cell cycle becomes significantly shorter compared to the absence of Ficoll. The slowed motile cells are also amenable for single-cell analysis of the activity of PSII (Fv/Fm). We therefore propose that the method developed here could serve as a sensitive monitoring system of the cell cycle changes and manipulation of cell motility mimicking the coral host environment, with concomitant single-cell photosynthetic activity analysis of Symbiodiniaceae.